Optimalisasi pemanfaatan limbah pertanian sebagai kompos bagi masyarakat Desa Tadangpalie Kabupaten Wajo - St. Fatmah Hiola; Army Auliah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Agriculture is the main income sector forTadangpalie villagers at Sabbangparu District, Wajo regency. The participants of the activity are the peasant community whoare members of the Abbanuange Gapoktan. The method usedin this activity through education and training with the aim atimproving farmers’ knowledge in the processing agriculturalwaste a quality organic fertilizer. Training was going well andin the family atmosphere. Material extension and how tomanufacture quality organic fertilizer were easily understoodby farmers. All farmers can make their own organic fertilizerfrom agriculture waste. Knowledge of farmers on organicwaste still needs to be improved to prevent environmentalpollution.